Impedance properties of biomass in support of practical mensuration in rain gardens - Jalilian, Farhad; Valeo, Caterina; Chu, Angus; Bhiladvala, Rustom (Frontiers in Sensors, 2023)
Impedance microbiology was explored to provide insights into how a sensor that can monitor the growth of bacteria in vegetated bioretention systems (rain gardens) may be designed for in situ, real-time use. The impedance properties of Pseudomonas Putida samples were monitored under AC signals of 100 mV peak-to-peak and sweeping frequencies of 20 Hz to 300 kHz, to determine relationships between these properties and biomass in the laboratory. The capacitance of the samples was found to be the most sensitive impedance parameter, with average change in magnitude of 37% due to bacterial growth. For verification, optical density measurements were taken and calibrated by direct hemocytometry counts of similar samples, simultaneously with the impedance testing. The experiments revealed that exponential relationships enable a good estimate of the biomass available in the medium, based on the change in capacitance. The detection range of the proposed system (in the range of tested strain) is approximately ~9.2×106 cells/ml to ~5×108 cells/ml.